2017
DOI: 10.1111/are.13298
|View full text |Cite
|
Sign up to set email alerts
|

Weaning methods using formulated feeds for snakehead ( Channa striata and Channa micropeltes ) larvae

Abstract: The culture of snakehead fish (Channa striata and Channa micropeltes) in Vietnam is limited, and snakehead culture has been banned in Cambodia, because traditional practices include capture of fingerlings from the wild as seed, as well as capture of small-size (also known as trash fish or lowvalue) fish. As hatchery breeding technology has improved, we investigated the optimal weaning practices for these two species. Both laboratory experiments and farm trials were conducted. For C. striata, the optimal weanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…Once the larvae start feeding fish mash profusely, 10%–15% grounded pellet feed suitable for the larvae (say CP 45%–50%, lipid 10%) has to be mixed in it with the gradual replacement of an equal amount of fish mash every day in such as manner that the fish mash is totally replaced with formulated diet within 7–8 days or in a maximum 10 days. Hien et al 108 have also reported more or less similar result with higher weight gain and low of cannibalism rate when the feeding was changed from live chopped fish with that of formulated feed at 10% daily replacement. This way the larvae could be weaned on a grounded formulated diet within 35 dph.…”
Section: Larval Rearingmentioning
confidence: 76%
“…Once the larvae start feeding fish mash profusely, 10%–15% grounded pellet feed suitable for the larvae (say CP 45%–50%, lipid 10%) has to be mixed in it with the gradual replacement of an equal amount of fish mash every day in such as manner that the fish mash is totally replaced with formulated diet within 7–8 days or in a maximum 10 days. Hien et al 108 have also reported more or less similar result with higher weight gain and low of cannibalism rate when the feeding was changed from live chopped fish with that of formulated feed at 10% daily replacement. This way the larvae could be weaned on a grounded formulated diet within 35 dph.…”
Section: Larval Rearingmentioning
confidence: 76%
“…Gambar 5. Pengukuran panjang dan bobot ikan gabus Studi tentang penggantian ikan rucah oleh pakan pellet pada ikan gabus menunjukkan tingkat pertumbuhan yang lebih baik dan lebih menguntungkan (Hien et al, 2015;Hien et al, 2016;Hien et al, 2017). Mengganti ikan rucah dengan pakan pellet memberi lebih banyak manfaat dalam biaya makan dan mengurangi ketergantungan pada pasokan ikan rucah.…”
Section: Gambar 4 Sampling Pemeliharaan Ikan Gabus Dalam Hapa 2x3unclassified
“…In intensive cultivation systems of carnivorous fish, low survival rates for fingerlings and juveniles are mainly attributed to the non-acceptance of formulated diets and high rates of cannibalism (Hien et al, 2017;Su et al, 2020). Such non-acceptance can be attributed to the dry texture and low palatability of formulated diets for this kind of fish (Perera et al, 2016).…”
Section: Introductionmentioning
confidence: 99%